Low-cost remotely operated underwater vehicle for underwater observation purposes - Wan Sabr, Wan Muhd Arif; Zabidi, Irfan Rahim; Abd Musthalib, Mohd Aliff; Muhamad, Zimam Amer; Mohd Hazman, Muhammad Irfan; Mohd Yusof, Muhammad Syafiq; Naing, Lwinthein; Zainal Abidin, Zulkifli (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper is about the development of a low-cost remotely operated underwater vehicle (ROV) for the observation of underwater environments without risking human life. The overall safety feature focuses on protecting internal circuits from being overloaded by any unexpected high current as well as protecting battery from being over-discharged to prolong the battery’s life. The robot has internal sensor to measure the battery voltage level along with its movement speed for safety precautions. It has a camera that sent underwater visuals to the users at the base station for underwater monitoring, observation, and exploration purposes. Floatable ballasts that hold adjustable volume of air are attached to the vehicle. The ROV has been tested on several locations for performance analysis, data collection, and navigation control; moreover, it has also won the first prize in T-Robotics Underwater Challenge organized by TSystem Malaysia.